Optimism on checkout: Emotional shifts and trust building in gen Z online shopping - Wangsa, Ignasius Heri Satrya (Seminar Nasional Penelitian dan Abdimas, 2025)
This study explores the emotional transformation experienced by Generation Z consumers in their journey of online shopping, focusing on the shift from initial skepticism and pessimism to trust and optimism. Drawing upon narrative analysis of ten firsthand accounts, the research identifies patterns of emotional progression influenced by repeated digital interactions, peer influence, and learning behavior. The study contributes to sustainability in e-commerce by highlighting how trust in digital platforms fosters more deliberate and potentially environmentally conscious consumption. The findings offer insights for marketers and platform developers to foster positive emotional engagement and long-term consumer relationships.